АНДРАГОГИК ЁНДАШУВ АСОСИДА МАЛАКА ОШИРИШ ЖАРАЁНЛАРИНИ ЛОЙИҲАЛАШТИРИШ - Мирсолиева, М.Т. (SCIENCE and SOCIETY, 2020)
The article discusses the socio-pedagogical necessity of the organization of adult education, the methodology of andragogy and eutago, the design of retraining and advanced training processes based on the andragogical approach, as well as the model of andragogic education in retraining and advanced training.